SHAPE EFFECT ON FREE VIBRATION OF FUNCTIONALLY GRADED PLATES - Kurtaran, Hasan (Akdeniz Üniversitesi, 2014)
In this article, shape effect on free vibration behavior of functionally graded plates is investigated. Square, rectangular, skew, circular, elliptical, annular and equilateral triangular plates with the same surface area and thickness are considered. Frequency values of these plates are compared for simply supported and clamped boundary conditions. Finite element method (FEM) is used in calculating frequency values and mode shapes. Since commercial codes do not allow inputting functionally graded material properties directly, MATLAB code was developed for FEM solution. Findings of this study can be useful for designers that have freedom to choose the plate shape in engineering applications